MENINGKATKAN KEMAMPUAN KOGNITIF MELALUI PERMAINAN ABACUS ANGKA USIA 3-4 TAHUN - Rukiati, Rukiati; Khotimah, Nurul (PAUD Teratai, 2016)
Abstract: This study usedaction researchclass.This purpose of this research is increasingcognitive abiliy throughabacus number game on 3-4 years old in KB Al-hikmah Sukorejo Perak Jombang .The subjects of this research is children have 3-4 years old in KB Al-hikmah Sukorejo Perak Jombang. While, the data analysis techniques used was descriptive statistical based on the reflection analysis of the cycle. The results of this research shows that there is significant cognitive ability in spelling number 1-5 get 37% based on avalution result from cycle I and cycle II. So can be conclused that  there is improving cognitive ability through Abacus Number Games the children have 3 ? 4 years. Keywords : Cognitive ability. Abacus number. Abstrak: Penelitian tindakan kelas ini bertujuan untuk meningkatkan kemampuan kognitif melalui permainan abacus angka usia 3-4 tahun di KB Al-hikmah Sukorejo Perak Jombang. Subjek penelitian adalah anak usia 3-4 tahundi KB Al-hikmah Sukorejo Perak Jombang. Teknik pengumpulan data penelitian ini menggunakan observasi dan dokumentasi sedangkan teknik analisis data menggunakan statistik diskriptif. Hasil penelitian menunjukkan adanya peningkatan kemampuan kognitif dalam membilang 1-5 sebesar 37% berdasarkan evaluasi hasil dari siklus I dan siklus II. Sehingga disimpulkan bahwa terjadi peningkatan kemampuan kognitif melalui permainan abacus angka pada anak usia 3 ? 4 tahun. Katakunci: Kemampuan kognitif,  Abacus angka.